2015
DOI: 10.1371/journal.pgen.1005344
|View full text |Cite
|
Sign up to set email alerts
|

Nmf9 Encodes a Highly Conserved Protein Important to Neurological Function in Mice and Flies

Abstract: Many protein-coding genes identified by genome sequencing remain without functional annotation or biological context. Here we define a novel protein-coding gene, Nmf9, based on a forward genetic screen for neurological function. ENU-induced and genome-edited null mutations in mice produce deficits in vestibular function, fear learning and circadian behavior, which correlated with Nmf9 expression in inner ear, amygdala, and suprachiasmatic nuclei. Homologous genes from unicellular organisms and invertebrate ani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 55 publications
3
26
0
Order By: Relevance
“…However, the intense coordinated circling behaviour demonstrated by mWAKE mutants can be seen in hyperaroused mice [8][9][10] . In addition, in our swim tests, mWAKE (-/-) and mWAKE (Nmf9/-) mutants swam vigorously without impairment and never had to be rescued from potential drowning, which contrasts with the findings of Zhang et al (2015) (Extended Data Video 2). Thus, our interpretation is that these and other phenotypes described for mWAKE (Nmf9/Nmf9) mutants stem from their hyperarousal, although we cannot rule out subtle vestibular dysfunction requiring specialized testing.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…However, the intense coordinated circling behaviour demonstrated by mWAKE mutants can be seen in hyperaroused mice [8][9][10] . In addition, in our swim tests, mWAKE (-/-) and mWAKE (Nmf9/-) mutants swam vigorously without impairment and never had to be rescued from potential drowning, which contrasts with the findings of Zhang et al (2015) (Extended Data Video 2). Thus, our interpretation is that these and other phenotypes described for mWAKE (Nmf9/Nmf9) mutants stem from their hyperarousal, although we cannot rule out subtle vestibular dysfunction requiring specialized testing.…”
Section: Discussionmentioning
confidence: 64%
“…The variability of the pronounced nighttime locomotor activity in mWAKE (-/-) and mWAKE (Nmf9/-) mutants was driven by intense stereotypic "circling" behaviour in a subset (~30-40%) of these animals (Extended Data Video 1). Related to this, mWAKE was previously identified as Nmf9, and mutations in this gene were noted to cause circling behaviour, which was interpreted to be due to deficits in vestibular function 6 .…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…We and others previously demonstrated that mWake mRNA expression is enriched in the SCN (Bell et al, 2020;Liu et al, 2014;Zhang et al, 2015). In mice, the SCN can be roughly divided into a ventrolateral region (as defined by Vip expression), a central region (as defined by Grp expression), and a dorsomedial region (as defined by arginine vasopressin/Avp expression), where the VIP + and GRP + regions receive direct projections from intrinsically-photosensitive retinal ganglion cells (ipRGC) in the retina via the retinohypothalamic tract (Altimus et al, 2008;Moore, Speh, & Leak, 2002;Welsh et al, 2010;Yan et al, 2007).…”
Section: Suprachiasmatic Nucleusmentioning
confidence: 89%
“…WAKE acts downstream of the circadian clock to promote sleep during the night, by inhibiting the excitability of arousal-promoting clock neurons at that time (Liu et al, 2014). This protein has a single mammalian ortholog, mWAKE/ ANKFN1/NMF9, which is enriched in the suprachiasmatic nucleus (SCN), the circadian pacemaker in mammals (Liu et al, 2014;Zhang et al, 2015). Our ongoing work on mWAKE suggests that the function of WAKE in regulating arousal by rhythmically modulating neural activity is conserved in mice.…”
Section: Introductionmentioning
confidence: 99%